Cultural implications through hand gesture in Japanese and Balinese communities - Imelda Imelda; Harisal Harisal (JPPI (Jurnal Penelitian Pendidikan Indonesia), 2024)
Communication involves verbal and non-verbal forms of expression, such as gestures. However, misunderstandings can arise when people from different cultures communicate. This research aims to examine the use of body movements by Japanese and Balinese people, exploring their similarities and differences. This research involves descriptive-qualitative analysis, data collection through observation, interviews, and recording. The method used for selecting these samples was purposive sampling. Findings suggest that both cultures have similar understandings of gestures due to their emphasis on social etiquette. Additionally, both cultures incorporate elements of taboo, honor, and status in their gestures. However, Balinese body language is influenced by the cultural concept of Rwa Bineda, while Japanese body language is more influenced by inyo.